Analysis of Four Scales for Global Severity Evaluation in Parkinson’S Disease - Chana-Cuevas, P (Nature Research, 2016)
Global evaluations of Parkinson’s disease (PD) severity are available, but their concordance and accuracy have not been previously tested. The present international, cross-sectional study was aimed at determining the agreement level among four global scales for PD (Hoehn and Yahr, HY; Clinical Global Impression of Severity, CGIS; Clinical Impression of Severity Index, CISI-PD; and Patient Global Impression of Severity, PGIS) and identifying which of them better correlates with itemized PD assessments. Assessments included additional scales for evaluation of the movement impairment, disability, affective disorders, and quality of life. Spearman correlation coefficients, weighted and generalized kappa, and Kendall’s concordance coefficient were used. Four hundred thirty three PD patients, 66% in HY stages 2 or 3, mean disease duration 8.8 years, were analyzed. Correlation between the global scales ranged from 0.60 (HY with PGIS) to 0.91 (CGIS with CISI-PD). Kendall’s coefficient of concordance resulted 0.76 (P<0.0001). HY and CISI-PD showed the highest association with age, disease duration, and levodopa-equivalent daily dose, and CISI-PD with measures of PD manifestations, disability, and quality of life. PGIS and CISI-PD correlated similarly with anxiety and depression scores. The lowest agreement in classifying patients as mild, moderate, or severe was observed between PGIS and HY or CISI-PD (58%) and the highest between CGIS and CISI-PD (84.3%). The four PD global severity scales agree moderately to strongly among them; clinician-based ratings estimate PD severity, as established by other measures, better than PGIS; and the CISI-PD showed the highest association with measures of impairment, disability, and quality of life. © 2016, The Author(s).